Interdisciplinary Vision of the Digitalized Future Energy Systems - Zhao Yang Dong (IEEE, 2021)
Global energy systems are transforming from fossil fuels to renewables, but the conventional electricity systems are so fragile that could lead to negative consequences such as soaring prices, rolling blackouts, security issues and delays to emission reductions. Confronting to these issues, electricity systems of the future will be vastly changed, dominated by new technologies and business models, increasingly digital and highly complex. Such transformation will be enabled by means to efficiently, stably and affordably distribute electrical power from many sources and storage points. Market design, policy, regulations, legislations, cyber security and politics are barely keeping up with advances in technologies, and energy technology choices have multi-generational implications for people and economies. These issues are global and to find a solution requires true systems thinking, informed by cutting-edge research. This paper envisages interdisciplinary digitalized future energy systems for emission reductions and proposes a 6-theme template to shape the future energy system. The six research themes have been designed such that the “whole is greater than the sum of the parts”. Each theme is informed by the others and the inter-linking of the six themes’ inputs and outputs will drive the outcomes and impacts of future energy systems.